Comparative study of different anticoagulants and coagulants in the evaluation of clinical application of platelet-rich plasma (PRP) standardization - Ali Hebni Alshehri, Amer Ali Awaji, Abdullah Joeri Aldossary, Nader Muneer Alharbi, Salah Mohammed Khwaji, Azeb Mesfer ALGhamdi; Husain Omar Al Mebari, Yousef mubti almarwani, Abdulaziz Sowalah S Almotairi, Turki hassan alamri, Faisal zouid almutairi, Abdalmuhsen Shalah Mashouh Al Otaibi (Journal of International Crisis and Risk Communication Research, 2024)
Background: Platelet-rich plasma (PRP) is a blood product obtained by concentration and separation of whole blood. Aim: We aimed to evaluate anticoagulants and coagulants' efficacy in platelet-rich plasma preparation, aiming to standardize methods for optimized clinical applications by examining their impact on platelet yield and quality. Materials and methods: We searched Electronic databases (PubMed, Web of Science, and the Cochrane library) with the following keywords: Anticoagulants, Coagulants, Clinical application, platelet-rich plasma standardization. Two authors independently screened the titles and abstracts of the search results. After deleting duplicate articles, the remaining studies were analyzed using inclusion criteria, obtaining full texts for assessment, and synthesizing the results. Main findings: EDTA anticoagulation treatments yielded the highest counts of platelets. WBCs were not contaminated in all of the pure-PRP samples, and a significant difference in the WBC counts was observed between ACD-A and heparin-anti-coagulated samples. Over all pooled subgroup analysis comparing heparin and EDTA on RBCs MDs 95%CI: 0.008[0.012, 0.028], subgroup WBCs 0.066[0.97,1.11] and platelets 522.09[0.26, 0.35], heterogeneity is detected among all pooled studies. Conclusion: Our meta-analysis highlights EDTA as the most effective anticoagulant for maximizing platelet counts in PRP preparation, with minimal WBC contamination. The superior platelet yield associated with EDTA underscores its potential as the anticoagulant of choice for PRP preparation, particularly in therapeutic applications requiring high platelet concentrations. These findings can guide clinicians in selecting anticoagulants to optimize PRP efficacy, thereby improving patient outcomes in regenerative medicine and other fields.